Adaptive finite-time attitude control for spacecraft with input quantization and measurement uncertainties. (May 2019) - Hou, Linlin; Sun, Haibin
The issue of adaptive finite-time attitude control is explored for rigid spacecraft with input quantization and measurement uncertainties, in which a hysteretic quantizer is introduced. The measurement uncertainties and external disturbances are compensated via adaptive control technique. By combining adding a power integrator technique with a new coordinate transformation, an adaptive finite-time controller is proposed to derive system states into a neighborhood of the origin in finite time. Finally, the control performance of the developed control scheme is demonstrated via simulation results.